EKSPERIMENTASI MODEL BLENDED LEARNING BERBANTUAN VIDEO PEMBELAJARAN DENGAN MEDIA WHATSAPP GROUP TERHADAP PRESTASI BELAJAR MATEMATIKA SISWA - Wulandari, Agustian; Maryam, Isnaeni; Darmono, Prasetyo Budi (UIN Imam Bonjol Padang, 2023)
This study aims to find out whether the blended learning model with the help of learning videos is better than the blended learning model with the help of whatsapp groups on the mathematics learning achievement of class XI MA Ma'arif NU Kaliangkrik students in the 2021/2022 academic year. This research is an experimental research using the posttest only control group design with data collection in this study using the cluster random sampling technique. The subjects of this study were grade 11 students of MA Ma'arif NU Kalingkrik who were taken from 2 classes. Data was collected using a mathematics learning achievement test that had been tested and met the reliability and validity requirements, then analyzed using the normality test, homogeneity test and hypothesis testing. The hypothesis test used is the t-test. Based on the results of the study, it can be concluded that the blended learning model assisted by learning videos is better than the WhatsApp group assisted learning model for students' mathematics learning achievement.